2019
DOI: 10.1002/aenm.201803766
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Defect Passivation for Perovskite Solar Cells by Controlling the Electron Density Distribution of Donor‐π‐Acceptor Molecules

Abstract: Organic–inorganic hybrid perovskite solar cells (PSCs) are a promising photovoltaic technology that has rapidly developed in recent years. Nevertheless, a large number of ionic defects within perovskite absorber can serve as non‐radiative recombination center to limit the performance of PSCs. Here, organic donor‐π‐acceptor (D‐π‐A) molecules with different electron density distributions are employed to efficiently passivate the defects in the perovskite films. The X‐ray photoelectron spectroscopy (XPS) analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
245
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(253 citation statements)
references
References 46 publications
8
245
0
Order By: Relevance
“…C12‐QDs tailored device achieves a higher V bi of 1.32 V, which is an indicator of reduced screening effect caused by charge carrier recombination. This is mainly attributed to the larger driving force (the energy levels of QDs are provided in Supplementary Figure S4) and reduced interface trap states . Furthermore, the larger slope of device tailored with C12‐QDs than that of other PSCs means a lower interfacial charge density, suggesting an improved charge extraction behavior.…”
Section: Figurementioning
confidence: 87%
“…C12‐QDs tailored device achieves a higher V bi of 1.32 V, which is an indicator of reduced screening effect caused by charge carrier recombination. This is mainly attributed to the larger driving force (the energy levels of QDs are provided in Supplementary Figure S4) and reduced interface trap states . Furthermore, the larger slope of device tailored with C12‐QDs than that of other PSCs means a lower interfacial charge density, suggesting an improved charge extraction behavior.…”
Section: Figurementioning
confidence: 87%
“…in which V TFL , e 0 , e, e and L represent the trap-filling limit voltage, vacuum permittivity,r elative dielectric constanta nd thickness of the perovskite film, respectively. [37,38] This directly indicated that the optimal mesoporous structure of film (6 h) was more favorable for effectively passivating the trap states density in the NiO/perovskite interface. Furthermore, the interfacial properties between NiON Ws HSC and perovskite film were furtherc haracterized by capacitance-voltage (C-V)m easurements.T he deduced Mott-Schottky curve ( Figure 3b)p rovides the built-in-potential (V bi )v alue of these devices (FTO/NiO/Perovskite/Ag).…”
Section: Resultsmentioning
confidence: 90%
“…The result indicates that the HOMO level of C 8 ‐BTBT (150 °C) is deeper than that of PEDOT:PSS, better matched with the valence band of CH 3 NH 3 PbI 3 perovskite (–5.4 eV). As a result, more efficient hole extraction from the perovskite layer and a lower energy loss can be expected, which leads to a higher V oc . Moreover, the higher lowest unoccupied molecular orbital (LUMO) level of C 8 ‐BTBT (–2.2 eV) will effectively block electrons, thereby reduce charge carrier recombination.…”
Section: Resultsmentioning
confidence: 99%
“…Organic‐inorganic hybrid perovskites have attracted tremendous attention due to their capabilities in appropriate band gap, high extinction coefficient, and long‐range photocarrier diffusion length, which opened up exceptionally rapid progress in power conversion efficiency (PCE) of the perovskite solar cells (PVSCs) in recent years …”
Section: Background and Originality Contentmentioning
confidence: 99%